Hubungan Pola Asuh dengan Kejadian Stunting pada Balita - Evicenna Naftuchah Riani; Wulan Margiana (Jurnal Kebidanan Harapan Ibu Pekalongan, 2022)
The results of the Indonesian Toddler Nutritional Status Survey (SSGBI) show that there is a decline in the stunting rate of 27.67 percent in 2019. Although the stunting rate has decreased, this figure is still quite high from the WHO target of no more than 20%. The prevalence of newborns experiencing stunting is 23%. The prevalence does not include babies born normally but due to lack of nutritional intake contributed to the increase in the prevalence rate to 27.6%. The stunting prevalence rate in Banyumas Regency in June 2021 was 14.2%. One of the causes of the high stunting rate in Banyumas Regency is the lack of knowledge and public awareness about various matters relating to child growth and development. Factors that are not good parenting in the family is one of the causes of the problem of nutritional intake needs. Parenting in the family includes several things such as breastfeeding, complementary foods, psychosocial stimulation, hygiene/hygiene practices and environmental sanitation, care for sick children. This study aims to analyze the relationship between parenting patterns and the incidence of stunting in toddlers in Baturaden, Banyumas Regency. The research design in this study was analytic observation, with a cross sectional approach. Collecting data using a questionnaire with a sample of 30 respondents. The results of the study found that there was a relationship between parenting patterns and the incidence of stunting in toddlers.